THE EFFECT OF VCO TO THE GROWTH OF CANDIDA ALBICANS ON DENTURE BASIS OF ACRYLIC RESIN - Vivi Indah Fatmasari; Rebriarina Hapsari; Nadia Hardini; Endang Sri Lestari (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Acrylic resin was a material of denture base which frequently used, but it still had a weakness that it was porous, then, it was often the breeding ground of Candida albicans. Virgin coconut oil (VCO) contained fatty acid which was effective to hamper the growth of C.albicans. Objective: This research was to identify the effect of VCO on the growth of C.albicans on acrylic resin denture. Methods: This research was an experimental laboratory research which exerted post-test control group design. The total sample 24 which were divided into 3 groups of treatment and 1 group of control. The treatment covered acrylic plates soaking which have been contaminated with C.albicans suspension into VCO in concentration level 25%, 50%, 75%, and sterile aquades for 8 hours. The acrylic plate was vibrated to knock out C.albicans and was then continued by colony counting on the media of Sabouraud Dextrose Agar (SDA). The statistic test employed Kruskal-Wallis and continued to the Post-Hoc test which employed Mann-Whitney. Findings: The VCO in concentration level 25%, 50%, and 75% affected to inhibit the growth of C.albicans. In the Kruskal-Wallis test, it was found a significant difference between the number of C.albicans on the control group and the VCO in concentration level 25%, 50%, and 75% (p<0,05). The Post-Hoc Mann-Whitney test indicated no significant difference between VCO in concentration level 25% and 50%, 25% and 75%, also 50% and 75% (p>0,05). Conclusion: The VCO in concentration level 25%, 50%, and 75% affected was able to hamper the growth of C.albicans. Further, there was no significant difference in each VCO concentration.